2019
DOI: 10.1186/s12881-019-0899-3
|View full text |Cite
|
Sign up to set email alerts
|

Uridine diphosphate glucuronosyl transferase 1A (UGT1A1) promoter polymorphism in young patients with sickle cell anaemia: report of the first cohort study from Nigeria

Abstract: Background (TA) n repeat sequence (rs8175347) of UGT1A1 gene promoter polymorphism is associated with serum bilirubin levels and gallstones among different sickle cell anaemia (SCA) populations. There are no data on UGT1A1 polymorphisms and their impact on Nigerian SCA patients. In this study, we determined the distribution of the UGT1A1 (TA) n genotypes among a group of young Nigerian SCA patients and healthy controls. In addition, the influence of UGT1A1 (TA) n genotypes on the laboratory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Parents and guardians of participants in a previous study on the clinical evolution of SCD among a young Nigerian cohort 17 at the study center were contacted through their telephone numbers and were asked to bring their wards for testing with the HemoTypeSC™ kits. The purpose of the study and the procedures were explained to the parents and participants in plain language.…”
Section: Methodsmentioning
confidence: 99%
“…Parents and guardians of participants in a previous study on the clinical evolution of SCD among a young Nigerian cohort 17 at the study center were contacted through their telephone numbers and were asked to bring their wards for testing with the HemoTypeSC™ kits. The purpose of the study and the procedures were explained to the parents and participants in plain language.…”
Section: Methodsmentioning
confidence: 99%
“…Four alleles are described in humans: (TA)5, (TA)6, (TA)7 and (TA)8. Low activity has been reported in humans with (TA) 7/7, 7/8 and 8/8 and normal or high activity in (TA) 6/6, 5/5, 5/6) [13]. The first part of this study showed that the most frequent β S haplotypes were the Benin haplotype (65.9% of the chromosomes) and the Bantu (20.5%) haplotype.…”
Section: Introductionmentioning
confidence: 46%
“…Initially, the literature search retrieved 1135 published articles. After exclusion of studies because of irrelevance and insufficient data to estimate the outcomes of interest, a total of 34 eligible studies published from 1977 to 2020, which met the eligibility for data extraction and analyses, were used for qualitative and quantitative synthesis; 15 studies from Africa, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 seven studies from the South America and North America, 42 , 43 , 44 , 45 , 46 , 47 , 48 seven studies from Asia, 8 , 49 , 50 , 51 , 52 , 53 , 54 and four studies from Europe. 55 , 56 , 57 , 58 Overall, this analysis included a total of 6771 SCD patients.…”
Section: Resultsmentioning
confidence: 99%